Examining gender equality, diversity, and inclusion: a case study of the challenges and opportunities in community extension programs in a select philippine university - Raton-Hibanada, Rowena; Castulo, Nilo Jayoma; de Vera, Jayson L.; Bituin, Analyn C.; Barcelona, Alvin B.; Zanoria, Iona Ofelia B.; Bedural, Zyralie L.; Bailon, James V.; Buenaventura, Ma. Laarni D.; Dellomos, Carl O. (Frontiers in Education, 2025)
This study investigated the mainstreaming of Gender Equality, Diversity and Inclusion (GEDI) principles into community extension programs carried out by a university as a case study, highlighting the extent of implementation, challenges, and opportunities. A qualitative case study design was employed, utilizing semi-structured interviews with eight faculty members from five campuses at Y University. Data were thematically analyzed to identify key challenges, opportunities, and evaluation measures for GEDI implementation. The findings revealed that metrics such as participation rates, qualitative feedback, and impact assessments serve as indicators of program effectiveness. Challenges include limited familiarity with GEDI, cultural resistance, and resource constraints that hinder effective integration. However, opportunities exist through needs-based assessments, stakeholder collaboration, targeted capacity-building programmes, and sustainability-focused initiatives. This study contributes to the limited research on GEDI integration into community extension programmes in higher education. This highlights the role of extension programs in promoting equity and inclusion and offers insights for improving program design and sustainability. This study was limited to one Teacher Education Institution (Y University) and had a small sample size. Future research should explore diverse institutional settings and develop sustainability metrics for integrating GEDI into community engagement initiatives.